SST Dynamics at Different Scales: Evaluating the Oceanographic Model Resolution Skill to Represent SST Processes in the Southern Ocean. Issue 4 (10th April 2019) - Skákala, Jozef; Smyth, Tim J.; Torres, Ricardo; Buckingham, Christian E.; Brearley, Alexander; Hyder, Pat; Coward, Andrew C.
Abstract: In this study we demonstrate the many strengths of scale analysis: we use it to evaluate the Nucleus for European Modelling of the Ocean model skill in representing sea surface temperature (SST) in the Southern Ocean by comparing three model resolutions: 1/12°, 1/4°, and 1°. We show that while 4–5 times resolution scale is sufficient for each model resolution to reproduce the magnitude of satellite Earth Observation (EO) SST spatial variability to within ±10%, the representation of ∼100‐km SST variability patterns is substantially (e.g., ∼50% at 750 km) improved by increasing model resolution from 1° to 1/12°. We also analyzed the dominant scales of the SST model input drivers (short‐wave radiation, air‐sea heat fluxes, wind stress components, wind stress curl, and bathymetry) variability with the purpose of determining the optimal SST model input driver resolution. The SST magnitude of variability is shown to scale with two power law regimes separated by a scaling break at ∼200‐km scale. The analysis of the spatial and temporal scales of dominant SST driver impact helps to interpret this scaling break as a separation between two different dynamical regimes: the (relatively) fast SST dynamics below ∼200 km governed by eddies, fronts, Ekman upwelling, and air‐sea heat exchange, while above ∼200 km the SST variability is dominated by long‐term (seasonal and supraseasonal) modes and the SST geography. Key Points: At 4‐5 times the resolution, each model resolution represents SST variability with an accuracy of >90% We classified scales of impact and identified the resolution requirement for different model input SST drivers Above ∼10 km one can split SST dynamics into two characteristic regimes with scale of separation at ∼200 km